Soft skills training and intervention in organizational crisis situations for better managerial outcomes in the delivering of bad news - Frasco, Beatriz Carmo Delgado Monteiro (2023)
This paper examines the impact of communication skills training in organizational crises to enhance managerial outcomes when delivering bad news. With the COVID-19 pandemic highlighting the need for reskilling, this study aims to develop a training model based on Kolb’s Experimental Learning Model, using SPIKES, NURSE and Bies’ Multiphase model as theoretical basis. To test the designed training, three pilot sessions were conducted, resulting in positive reaction and knowledge retention from the participants. This research ultimately contributes to enhancing manager’s skills in crisis communication, offering practical recommendations for future trainings